Материалы к изучению биографии и творчества Михаила Горлина из архива Institut d’études slaves (Париж): Часть вторая (№ 6) [Materials Pertaining to the Life and Works of Mikhail Gorlin from the Archive of the Institut d’études slaves (Paris). Part 2 (No 6)] - Fedor Poljakov (Slavica Revalensia)
The publication features some of the heretofore unknown materials on the history of Russian literature in exile from the archive of the Institut d’études slaves (Paris). These documents are related to Mikhail Gorlin (1909—1942), a poet, scholar, and employee of the Institute who worked there until the repressions following the occupation of France in 1940, which eventually led to his murder at Auschwitz in 1942. The article presents some documents and testimonies shedding light on Mikhail Gorlin’s last years in Berlin (early 1930s), in particular commenting upon the biography of Vladimir Postman, a lesser-known participant of Gorlin’s literary association. The published documents are accompanied by literary-historical annotations.